Poland’s financial sector development in terms of global financial transformations - Marena, Tetyana (Research Papers in Economics and Finance, 2020)
The paper deals with the study of global financial transformations impact on the financial sector in Poland. Two types of tendencies of the global financial space development that create new conditions for national financial systems are defined,including: trends that lead to qualitative shifts in countries’ financial systems and do not necessarily imply a negative impact on the national financial systems; threatening challenges that shatter financial markets and restrain their sustainable development. The current positions of Poland’s financial sector in the world and regional financial systems are evaluated. The shifts in the national financial sector in terms of global financial transformations are found out. It is stated that while integrating into the global financial space, Poland will increasingly feel the impact of global transformations that will determine further scenarios for the domestic financial sector development. Exogenous factors that can aggravate challenges threatening the stability of Poland’s financial sector in the near future are identified.